THE EFFECT OF CASUMBA TURATE (Carthamus Tinctorius L) ON PERINEAL WOUND HEALING OF GALIST WISTAR - muliana aras; Runjati Runjati; Sakundarno Adi (International Journal of Nursing and Health Services (IJNHS), 2019)
Perineal injury is one of the most common causes of first birth and results in perineal tears, which categorized into four degrees, including stage I, stage II, stage 3 III, and stage 4 IV. The study aimed to examine the effect of the casumba turate extract ointment (Carthamus tinctorius L) on improving the perineal wound healing among Wistar (Rattus norvegicus). An experimental laboratory test with a randomized control trial in the post-test only with control group design was applied in this study. Thirty-two samples comprised of experimental group (n=16) and control group (n=16) were involved in this study. REEDA scores using the Mann Whitney test analysis were used to determine the progress of perineal wound healing. The results showed that there is a significant difference in mean score between intervention and control group after implementation of the casumba turate (p <0.05). In conclusion, casumba turate extract 5% ointment has a positive impact on the wound healing process for perineal of Wistar (Rattus norvegicus). Keywords: casumba turate, perineal wounds, Wistar